Performance art : from futurism to the present - Goldberg, RoseLee; Goldberg, RoseLee; Goldberg, RoseLee (London ; New York : Thames & Hudson, 2011)
First published in 1979, the latest edition of this pioneering study in'the World of Art' series surveys a full century of performance, from the Futurist manifesto of 1909 to the second decade of the new millennium. Art historian and gallery curator Rose Lee Goldberg explains how a medium once used only in sporadic outbreaks of artistic dissent has become, over the course of a century, a vital and integral part of the contemporary mainstream and a global phenomenon.
Futurism -- Russian futurism and constructivism -- Dada -- Surrealism -- Bauhaus -- Living art c. 1933 to the 1970's -- The art of ideas and the media generation 1968 to 2000 -- The first decade of the new century 2001 to 2010.
Originally published in large format as Performance : live art 1909 to the present. First published in paperback in the United States of America by Thames & Hudson Inc., ... New York'--T.p. verso.
Previous published as Performance : live art since 1960. New York : Harry N. Abrams, 1998. Previously published as a rev. & expanded ed. as Performance art : from futurism to the present. New York : Thames & Hudson, 2001.
Includes bibliographical references (p. 250-252) and index.
Keywords: Performance art; Arts, Modern -- 20th century; Arts, Modern -- 21st century; Group work in art